Discussing the Effect of Students' Crisis Awareness on Emotion During the COVID-19 Pandemic From the Perspective of Trust - Yang, Cheng; Miao, Yinghua (Frontiers in Psychology, 2022)
The effects of crises vary among individuals, societies, and nations. Governments' crisis management is quite different from that of non-governmental organizations, especially in terms of “publicity,” since it involves bureaucracy to address people's accountability concerns. The purpose of this study is to investigate the relationship between students' crisis awareness, trust, and emotions in the event of a major public health emergency. A questionnaire survey was conducted for this study. A total of 500 copies of questionnaires were distributed to the college students in Jiangxi. Among those, 437 valid copies were retrieved, with a retrieval rate of 87%. A structural equation model (SEM) was used to conduct the statistical analyses. The research results were summarized as follows: (1) At the stage of epidemic spread, people can easily fall into the negative emotion. (2) The society with a good trust relationship considers schools less responsible for critical incidents and more helpful for crisis communication. (3) Reducing the negative emotions of the public after the occurrence of critical incidents can effectively reduce the damage of critical incidents to the organization. Avoiding a loss of student confidence and increasing anger, protecting the school's reputation, having a good communication effect, and minimizing the impact of the crisis can help the students develop better trust toward the school. When a crisis occurs on campus, this can reduce the possibility of students' showing negative emotions and spreading rumors. It is considered that the findings provide guidance on how to optimize the management of public health crisis situations and improve students' mental health.